PREPARATION OFPAVEMENTBLOCK BY USING WATSE MATERIAL (International Journal of Engineering Management Science, 2024)
The aim of this project is to innovate in the construction industry by replacing cement with plastic waste in pavement blocks, thus reducing production costs and addressing the mounting issue of plastic waste. With approximately 56 lakh tons of plastic waste generated annually in India and its slow degradation rate, finding sustainable ways to manage this waste is imperative. This project explores the incorporation of plastic waste in varying proportions along with artificial sand and overburnt bricks as coarse aggregates to produce pavement blocks. Overburnt bricks, often deemed unusable in conventional construction due to their dark red color and distortion, possess qualities beneficial for pavement block production, such as increased strength, lower absorption, and higher density. By utilizing these materials, we aim to not only reduce plastic waste but also repurpose overburnt bricks, contributing to a more sustainable and cost-effective approach to pavement block manufacturing.
Keywords: Plastic waste, overburnt bricks, pavement blocks, sustainable construction, waste management, alternative materials, mechanical properties, durability, environmental impact, recycling